Sociopreneurship Incubation Class for School Dropouts in Bajoe Village Through the Utilization of Sea Shells into Economically Valuable Products - Rahmadania, Lisa; Wahyuni, Sri; Nurisharyanti, Nurisharyanti; Riski, Muh.; Miftahul Jannah, Ahlia (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
A sociopreneurship-based business incubation program aims to empower school dropouts in Bajoe Village through skills training in utilizing seashells as raw materials for economically valuable craft products. This initiative was motivated by the high school dropout rate in Bone Regency, particularly in Bajoe Village. This has the potential to lead to unemployment and low quality human resources. This research used a qualitative descriptive approach with community service methods. The program’s subjects were 10 school dropouts selected purposively. Data collection techniques included observation, interviews, documentation, and questionnaires. The results showed that participants understood the production and marketing processes for seashell craft products. The program also improved participants’ entrepreneurial skills, producing products such as key chains and flower vases ready for offline and online marketing. Based on post-training questionnaires, participants demonstrated increased motivation and readiness to continue their businesses independently. This program demonstrates that sociopreneurship-based training can be an alternative solution for empowering school dropouts through local potential.